Socialização infantil para o perdão: o lugar da empatia materna nesse processo - Melo, Rômulo Lustosa Pimenteira de (2019)
The purpose of this thesis was to verify whether maternal empathy can explain maternal parenting styles, the child's empathy and the beliefs of mothers and children about forgiveness, and it was developed in four theoretical chapters and two empirical articles. It follows three main theoretical framewoks, Maccoby and Martin’s, that describes how the process of children’s socialization by the parents occurs; Martin L. Hoffman’s, which conceptualizes and shows how the development of empathy can happen, and finally, the theoretical framework about interpersonal forgiveness from the perspective of Enright and the Human Development Study Group. Considering the attribute of interpersonal forgiveness in enhancing interpersonal relationships and improving mental health, this study has as main question to verify if mothers could socialize their children to present better attitudes towards interpersonal forgiveness. That is, is there childhood socialization for forgiveness? We will argue that the answer is positive and that it passes through maternal empathy, which is important for parental styles of acceptance and implication, and fosters the empathy of children, which thereby favor more guidance of children for forgiveness. Therefore, our thesis is that maternal empathy, through maternal socialization, is an element that stimulates the children's positions towards forgiveness. The analyzes of the two empirical articles were carried out mainly through structural equation modeling. In the first article it was proposed to seek evidence of factorial validity and internal consistency of two measures of forgiveness, one of agreement with forgiveness as a way of solving interpersonal problems and another of attitudes with forgiveness to resolve these conflicts. Three studies were carried out, the first and second ones with independent samples of 200 university students and the third one with a sample of 400 women and their children. It was shown as best fit a bifactor structure, of two sets of four opposing factors, with four relating to the events of injustices and four relating to the persons involved in the hurtful situation. The results show that the reasoning of forgiveness is explained by two sets of distinct latent variables, the type of injustice and the perpetrator. The second article presents the results that directly answer the purpose of the study. After confirmation of the forgiveness measure, the second study was continued. It was employed a sample of 400 mothers and their children, all of them attending high school in the interior of Paraíba - Brazil. The mothers' responses to the forgiveness scales, the empathy scales (Interpersonal Reactivity Index) scales and a demographic questionnaire were used. The children answered the Parental Socialization Scale in Adolescence (ESPA 29), the empathy scale (Interpersonal Reactivity Index), the forgiveness scale and a sociodemographic questionnaire. The results confirmed the implication of maternal empathy in the entire process of child socialization for forgiveness. In addition, it was also found that the child's empathy mediates the relationship between the acceptance / implication dimension of socialization and their belief about forgiveness. Another result to be mentioned was the conservation of the congruence of guidance on forgiveness between the mothers and their children. Finally, it is considered that the results corroborate the defended thesis and contribute to the expansion of the models of socialization focused on moral development.